Global Library and Information Science - Abdullahi, Ismail (IFLA Publications ;, 2017)
This 2nd edition of the highly successful Global Library and Information Science presents an up-to-date review of international librarianship and library science through insightful and well written chapters contributed by experts and scholars from all regions of the world. The role of public, academic, special, school libraries, as well as library and information science education are presented from the early development to the present time. Its lively, readable approach will help the reader to understand librarianship in Africa, Asia, Australia and New Zealand, Europe, Latin America and the Caribbean, and North America.Edited by Ismail Abdullahi, Professor of Global Library and Information Science, this book is a must-read by library science students and teachers, librarians, and anyone interested in Global Librarianship.